2014
DOI: 10.5830/cvja-2014-038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rosuvastatin on ADMA, rhokinase, NADPH oxidase, caveolin-1, hsp 90 and NFkB levels in a rat model of myocardial ischaemia-reperfusion : cardiovascular topic

Abstract: SummaryAimEndothelial dysfunction, oxidative stress and inflammation are among the most important mechanisms of ischaemia–reperfusion (I/R) injury. Besides their cholesterol-lowering effects, statins are known to provide protection against myocardial dysfunction and vascular endothelial injury via nitric oxide-dependent mechanisms. The aim of this study was to investigate the effects of rosuvastatin on certain intermediates involved in the generation of nitric oxide (asymmetrical dimethyl arginin, ADMA, caveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Moreover, ROS activate other molecules, such as COX isoforms that also contribute to endothelial dysfunction 73 ; all of which are facts that support the current findings. On the other hand, the aptitude of Sim for reducing Nox activity, lipid peroxidation, ET-1/ERK 1/2 signal and COX-2 enzyme, as well as the enhancement of the defense molecule coincides with previous reports 59 , 74 , 75 and highlights its anti-oxidant and anti-inflammatory effects that are partially responsible for its cardioprotective effect against 5-FU.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, ROS activate other molecules, such as COX isoforms that also contribute to endothelial dysfunction 73 ; all of which are facts that support the current findings. On the other hand, the aptitude of Sim for reducing Nox activity, lipid peroxidation, ET-1/ERK 1/2 signal and COX-2 enzyme, as well as the enhancement of the defense molecule coincides with previous reports 59 , 74 , 75 and highlights its anti-oxidant and anti-inflammatory effects that are partially responsible for its cardioprotective effect against 5-FU.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that the NFκB signaling pathway is activated during I/R which leads to inflammatory response [ 27 ]. The Rel A p65 subunit involved in this pathway is up-regulated in injured hearts [ 28 ] and the depletion of p65 protects the injured heart [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that there is a link between Foxo3 and NFκB signaling, both of which play important role in anti-apoptosis and oxidative stess [ 27 , 43 ]. In an aging related study, Salminen et al reported that Foxo signaling acted as an antagonist of NFκB [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The S group and I/R group were given normal diet. The I/R + RSV group was administered RSV dissolved in distilled water via oral gavage at a dose of 10 mg/kg/day for 7 days continuously [ 12 , 13 ], the I/R + DGZ group received 1 mg/kg/day DGZ dissolved in distilled water by oral gavage for 7 days continuously [ 11 ], and the I/R + RSV + DGZ group received RSV 10 mg/kg/day and DGZ 1 mg/kg/day simultaneously via oral gavage for 7 days consecutively. The animals were forbidden to feed overnight before experiment, but were given free access to water.…”
Section: Methodsmentioning
confidence: 99%